Ultrasmall C-TiO2−x nanoparticle/g-C3N4 composite for CO2 photoreduction with high efficiency and selectivity. Issue 43 (29th October 2018) - Zhou, Jie; Wu, Han; Sun, Chun-Yi; Hu, Cheng-Ying; Wang, Xin-Long; Kang, Zhen-Hui; Su, Zhong-Min
Abstract : A three-component photocatalyst (C-TiO2− x @g-C3 N4 ) is designed with polyoxotitanium as a precursor which exhibits excellent performance towards in converting CO2 to CO under H2 O vapor via coupling with a two-electron/two-step oxidative pathway. Abstract : The photoreduction of CO2 to CO offers a promising sustainable and clean approach for a global new energy program. Coupling this reductive process with a matched water photo-oxidation pathway is an attractive avenue to accelerate the half-reaction of CO2 reduction. Herein, we propose a three-component photocatalyst design strategy for reducing CO2 to CO coupled with water oxidation via a two-electron/two-step pathway. Employing polyoxotitanium ([Ti17 O24 (OPr i )20 ]) as a titanium source, ultrasmall TiO2− x nanoparticles coated with ultrathin carbon layers (C-TiO2− x ) were fabricated and loaded on to a g-C3 N4 matrix through chemical bonding (C-TiO2− x @g-C3 N4 ) for the first time. The optimized C-TiO2− x @g-C3 N4 photocatalyst showed a very high activity of 12.30 mmol g −1 (204.96 mmol gTiO2 −1 ) CO generation within 60 h visible-light irradiation, which represents the highest CO production rate to date among the reported TiO2 -based materials under similar conditions. The excellent adsorption capability of C-TiO2− x @g-C3 N4 for photons, H + protons, and CO2 molecules together with efficient charge separation and the two-electron/two-step oxidative pathway lead to the high reactivity.